Faktor-Faktor yang Mempengaruhi Nasabah Terhadap Kepercayaan pada PT. Pegadaian Syariah Cabang Banda Aceh - Syamsul Rizal (Journal of Law and Economics, 2022)
company to its customers. With good service to customers or customers, it is expected to work productively, thus providing benefits to the company. The purpose of this study was to determine the magnitude of the influence of Customer Trust on Sharia Pawnshops who were involved as respondents in this study as many as 1,175 respondents, who were customers of the Banda Aceh Sharia Pawnshop Branch. Primary data was obtained using a closed questionnaire based on a Likert scale. used multiple linear regression analysis (Multiple Regression) with the formula Y = a + b1 X1 + b2 X2 + b3 X3 + e. The results of the study indicate that customer service has a significant influence on employee performance. This is indicated by the f-count of 5.277 and the f-table of 1.987. Judging from the magnitude of the correlation coefficient (R) is 0.754.71 and the magnitude of the coefficient of multiple determinants (R2) is 0.3,708. This shows that with the correlation (R), it means that the Customer Trust variable has a direct relationship with the performance of the Sharia Pawnshop employees while the R2 value means that the influence of Service on the Sharia Pawnshop Company Trust is influenced by other factors such as the speed of service and customer convenience which also greatly influences the research.